2012
DOI: 10.1111/j.1365-2672.2012.05387.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wet heat treatment on the germination of individual spores of Clostridium perfringens

Abstract: Aim To analyse the effect of wet heat treatment on nutrient and non‐nutrient germination of individual spores of Clostridium perfringens. Methods and Results Raman spectroscopy and differential interference contrast (DIC) microscopy were used to monitor the dynamic germination of individual untreated and wet heat‐treated spores of Cl. perfringens with various germinants. When incubated in water at 90–100°C for 10–30 min, more than 90% of spores were inactivated but 50–80% retained their Ca2+‐dipicolinic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 48 publications
(149 reference statements)
1
19
1
Order By: Relevance
“…Indeed, there is one report that spores incubated at lower temperatures for longer periods germinate more slowly than untreated spores (12). In addition, spores heat treated at even higher temperatures (ϳ90°C) that retain DPA and at least some viability germinated more slowly than untreated spores (19,20,29). However, the surprising result obtained with purified wild-type B. megaterium spores that had been incubated at 75°C was that they germinated more rapidly than untreated spores (Fig.…”
Section: Resultscontrasting
confidence: 46%
“…Indeed, there is one report that spores incubated at lower temperatures for longer periods germinate more slowly than untreated spores (12). In addition, spores heat treated at even higher temperatures (ϳ90°C) that retain DPA and at least some viability germinated more slowly than untreated spores (19,20,29). However, the surprising result obtained with purified wild-type B. megaterium spores that had been incubated at 75°C was that they germinated more rapidly than untreated spores (Fig.…”
Section: Resultscontrasting
confidence: 46%
“…These differences may reflect strain‐dependent heterogeneity of spore germination times ( T LYS ), as observed in previous studies . Despite these strain differences, the results under our growth‐promoting nutrient‐rich conditions are consistent with previous observations of C. perfringens using differential interference contrast microscopy, which have shown that sublethal heating stimulates the rate and extent of KCl‐induced spore germination .…”
supporting
confidence: 91%
“…It has been shown previously that the heat treatment intensity (time and temperature combination) has a (proportional) impact on germination and outgrowth behaviour of spores (Stringer et al, 2011;Wang et al, 2012). In these studies on heterogeneity in spore germination and outgrowth relatively mild heat treatments in the range of 70 to 90°C aiming for heat activation and/or reducing heterogeneous behaviour in the B. subtilis (Smelt et al, 2008) and C. botulinum (Stringer et al, 2011) spore population were applied.…”
Section: Number Of Observationsmentioning
confidence: 99%